L’interprétation sociale, une interdiscipline face à ses théories - Vermeiren, Hildegard (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article intends to contribute to the theoretical status questionis concerning social interpreting. Starting point is the very name of the discipline, which refers to sociology as well to communication and linguistics. The purpose is to examine how each of these research areas offers a number of concepts relevant to social interpreting, in particular those concepts referring to the category “subject”. The path that we have chosen is twofold. First we explore the development of each of these disciplines and the ensuing creation of relevant concepts for our topic of investigation. Next, we analyse how these three sciences have learned and borrowed from each other and what the relevance of this can be for research into social interpreting. We conclude the article with a schematic overview showing the corresponding relevant concepts placed next to each other.